The relationship of climate change & major events in Austria. (June 2021) - Burton, Anna; Fritz, Oliver; Pröbstl-Haider, Ulrike; Ginner, Kathrin; Formayer, Herbert
Abstract: Major events have increasingly become the subject of tourism destination promotion and have grown in importance in driving tourism demand in recent years. However, the staging of major tourist events has not only led to increased CO2 emissions in Austria, the events themselves have also been affected by climate change. The paper at hand is based on a data collection and review process which covered the relevant peer reviewed and grey literature. This comprehensive process was based on, and was open to, contributions by the full scientific community of relevant Austrian researchers and experts. The compilation process of the report followed quality standards such as the involvement of international partners as review editors within the review process. In addition, the literature was surveyed to integrate the international state of the art. The paper discusses the relationship between events and climate change by looking at mitigation measures on the one hand as well as adaptive strategies taken by event organizers on the other. However, a significant lack of objective information and data as well as appropriate scientific studies also became obvious in this process. Against this background main tasks and challenges for further research are identified and discussed. The paper closes with managerial implications for the organization of major events. Management implications: The literature review and the analyses of case study reports on events support the following suggestions:· - Climate change mitigation measures and environmental issues should be already a significant part of the call, the following application by the destination and the final decision making. - The application of specific environmental and climate friendly guidelines, awards or certificates are helpful tools to motivate the branch and to achieve "green" events. - Measures related to transportation and mobility are crucial to achieve significant savings of greenhouse emissions. - Further important aspects to be considered are waste management, catering, communication, accommodation and site selection. - Climate research may help to define a suitable period for the event at the desired location which is likely to avoid or reduce possible climate change related risks such as extreme heat or lack of snow.